Effect of integrated nutrient management on productivity of maize (Zea mays L.) and residual fertility status of soil - Yadav, R.K; Verma, A.; Nepalia, V.; Yadav, S.L. (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif 2011 in the Long Term Fertilizer Experiments initiated in kharif, 1997 at the Instructional Farm, Rajasthan College of Agriculture, Udaipur with maize.The highest grain yield (39.12 q ha-1) was recorded by application of 100% NPK + FYM 10 t ha-1 and its performance was at par with 150% NPK (Table 1). The treatment receiving 100% NPK and its combination with Zn, S, Zn+S, Azotobacter seed treatment and FYM 10 t ha-1 + 100% NPK (-NPK of FYM) showed statistically equivalent results in raising grain yield over the other treatments. Though application of 100% N, 100% NP, and FYM 20 t ha-1 increased the yield significantly over control but provided inferior results in comparison to aforesaid treatments. Similarly application of FYM 20 t ha-1 and 100% N alone were statistically at par with other but statistically superior over unfertilized control but provided inferior results in comparison toaforesaid treatments.